Bugs that rule the world [videorecording (DVD)] - Shultz, Doug; Obi-Melekwe, Nkeki (PBS, 2025)
The journey into the world of insects showcases the planet's most populous but least appreciated creatures. Scientists and enthusiasts around the globe explore the beauty and complexity of bugs, discovering cunning adaptations and bizarre behaviors. Investigations into a worldwide insect "apocalypse" highlight the critical roles bugs play and the bleak picture of a future without them.